Removal of Natural Organic Matter (NOM) from Aqueous Solutions by Multi-Walled Carbon Nanotube Modification with Magnetic Fe3O4 Nanoparticles - Abbas Khodabakhshi; Ayoub Riahi Farssani; Morteza Sedehi; Mehraban Sadeghi (International Journal of Chemical Engineering)
Backgroundand Aim. Natural organic matter (NOM) has become one of the most serious environmental problems due to its persistence in aqueous solutions and the risk of carcinogenesis. In this study, the removal efficiencies of real and synthetic humic acid (HA) by multi-walled carbon nanotubes (MWCNTs) coated with iron oxide were evaluated. Materials and Methods. The MWCNs were synthesized and coated with iron oxide. In addition, the effects of pH, contact time, mixing speed, and adsorbent dose on the removal efficiency of NOM by MWCNTs-Fe3O4 were studied. Then, the removal efficiency of NOM from real samples was investigated at optimal conditions. The MWCNT-Fe3O4 was characterized by scanning electron microscopy (SEM) test and X-ray diffraction (XRD), respectively. Data analysis was performed using Minitab software based on the Taguchi method. Results. The results showed that MWCNTs were coated with Fe3O4. The SEM test shows particle (MWCNTs-Fe3O4) size in the range of 48–143 nm, and the particles have uniform spherical shapes. Enix software was used to identify the phase in this sample. The conditions including pH=3, mixing speed = 120 rpm, adsorbent dosage = 1.5 g·L−1, and contact time = 90 minutes were selected as optimal for NOM adsorption. The mean removal efficiencies of NOM in synthetic samples at 5, 10, and 20 mg·L−1 concentrations were 86.6%, 84.87%, and 95.41%, respectively. In addition, the mean removal efficiency of NOM in Choghakhor Wetland was 77%. Conclusion. Our findings demonstrated that the MWCNTs-Fe3O4 can be potentially used as an adsorbent for removing natural organic matter (HA) from aqueous solutions.